2009
DOI: 10.2220/biomedres.30.287
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lower urinary tract symptoms and urinary ATP in patients with benign prostatic hyperplasia or overactive bladder

Abstract: We investigated whether the improvement of lower urinary tract symptoms (LUTS) and urinary adenosine triphosphate (ATP) level were related. Fifty-seven patients and 13 normal controls were enrolled in this study. All of the male patients had benign prostatic hyperplasia (BPH), and all of the female patients had overactive bladder (OAB). We administered an alpha-1 adrenergic receptor antagonist (tamsulosin hydrochloride) for BPH, while OAB patients received an anti-muscarinic agent (propiverine hydrochloride). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 19 publications
1
32
2
Order By: Relevance
“…Investigators found that urinary ATP was a better predictor than urinary NGF for detrusor overactivity in OAB [99]. Urinary ATP levels in OAB patients decreased after treatment with antimuscarinics [100], and a higher pretreatment urinary ATP level predicted a better response to antimuscarinic therapy. However, the sources of the urinary ATP (e.g., whether from the urothelium, suburothelium, nerves, and/or muscles) were not identified in these studies.…”
Section: Urothelial Abnormalities In Nonneurogenic Idiopathic Oabmentioning
confidence: 99%
“…Investigators found that urinary ATP was a better predictor than urinary NGF for detrusor overactivity in OAB [99]. Urinary ATP levels in OAB patients decreased after treatment with antimuscarinics [100], and a higher pretreatment urinary ATP level predicted a better response to antimuscarinic therapy. However, the sources of the urinary ATP (e.g., whether from the urothelium, suburothelium, nerves, and/or muscles) were not identified in these studies.…”
Section: Urothelial Abnormalities In Nonneurogenic Idiopathic Oabmentioning
confidence: 99%
“…These studies indicate that urothelial ATP release could play a key role in both volume-and noxious stimulus-evoked reflexes. In fact, an excess of urothelial ATP release was detected in interstitial cystitis or overactive bladder, conditions accompanied by visceral hyperesthesia leading to frequent urination or bladder pain (2,(28)(29)(30). However, the precise signaling cascade involved in the pathological increase of urothelial ATP release remains unknown.…”
mentioning
confidence: 99%
“…In fact, an excess of urothelial ATP release was observed in interstitial cystitis (4,23,24). In a group of female overactive bladder patients, those with a high ratio of urinary ATP/creatinine showed a higher symptom score of urinary frequency than those with a low ratio (22). Therefore, elucidation of the molecular mechanisms underlying urothelial ATP release would contribute to drug development for the therapeutic alleviation of storage symptoms or bladder pain.…”
mentioning
confidence: 99%